Towards a Scholarship of School-Based Teaching and Learning That Embraces Hope, Change, and Social Justice in a South African University - Moeng, Muki S. (Journal of Contemporary Issues in Education)

(untitled) (University of Alberta, 2022)
In this commentary, the author presents an argument for embracing a critical southern paradigm and framework for a Scholarship of Teaching and Learning (SoTL) that advances decoloniality, social justice, and conscientisation. The kind of scholarship that is argued for in this paper proposes a SoTL that goes beyond the recognition of classrooms as sites of inquiry and teaching, but a SoTL that is generative, context responsive, carries moral and pedagogical imperatives, and can influence institutional and societal change. This commentary draws on the experiences of a Dean of Faculty through self-reflexive qualitative impressions. She frames her personal experience of implementing a School-Based Learning placement approach within a theoretical discussion of agency, conscientisation, and transformative learning.